Potential damages, seasonal abundance and distribution of Empoasca terminalis Distant (Homoptera: Cicadellidae) on soybean in South Sulawesi - Nasruddin, Andi; Fattah, Abdul; Baco, Muhammad Said; Said, Ahwiyah Ekawati (Jurnal Entomologi Indonesia, 2014)
Plant damages caused by leafhopper, Empoasca terminalis Distant (Homoptera: Cicadellidae) on soybean were first encountered in 2007 in Makassar, South Sulawesi. The insect has been constantly associated with soybean crops in the province ever since. The purposes of the present study were to (i) evaluate potential yield loss attributable to the leafhopper in an experimental set up, (ii) seasonal abundance of E. terminalis, and (iii) distribution of E. terminalis in all major soybean-producing areas in the province. Potential yield loss due to the leafhopper was assessed in a field experiment using two large plots. One of the plots was kept leafhopper-free by weekly insecticide sprays; and the other plot was left unsprayed to allow leafhopper infestation to occur. Adult abundance was weekly monitored using a sweep net throughout the season. Nymph abundance was determined by direct count on the plant leaves. Leafhopper distribution was assessed through surveys conducted in all major soybean-producing areas in South Sulawesi, from 2009–2013. The results of the study showed that E. terminalis caused an average yield loss of 26% on susceptible crops without insecticide use. First leafhopper infestation in all planting seasons occurred two weeks after the plant emergence. Rainfall negatively correlated with the leafhopper abundance. The leafhopper existed in all major soybean production areas in the province. Therefore, our results confirmed the status of E. terminalis as an important soybean pest in the region. In addition, crops planted early in the dry season could escape from heavy leafhopper infestation.